Analisis Permintaan Pariwisata Indonesia : Studi Kasus 6 Negara di Kawasan Asia Pasifik Tahun 2009-2015 - Agesti, Frida Ayu (Jurnal Ilmiah Mahasiswa FEB, 2017)
Tourism has shifted as human's basic necessity in this modern era. Data show that world's tourism demand rises in every year, and so does in Indonesia. A significant rise took place in the years of 2009-2015 with the biggest demands coming from countries within the Asia Pacific region like Singapore, Malaysia, Australia, China, Japan, and South Korea. According to demand theory, variables that influence tourism demand are Nominal Exchange Rate, Consumer Price Index (CPI), GDP Per Capita and Population.Data from those six countries from 2009-2015 were examined using data panel analysis in order to identify the effect that Nominal Exchange Rate, Consumer Price Index, Per Capita PDB, and Population have towards tourism demand. Tourism demand is determined by the total number of foreign tourists coming to Indonesia. The result shows that every one of the variables have positive impact on Indonesian tourism demand.Keyword : Tourism Demand, Exchange Rate, CPI, GDP Per Capita, Population, Data Panel